Interactive Visualizations to Support Randomized Clinical Trial Monitoring - Rey, Marina Fortes; Freitas, Carla M. D. S. (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI); 2021: Anais da XXXIV Conference on Graphics, Patterns and Images, 2021)
Despite current technological advances, interactive tools to facilitate the analysis of data collected during clinical trials are still not widely available. Such a scenario makes researchers rely on time-consuming extractions from databases and subsequent application of analytical methods by statisticians to obtain results from which they can get insights. Moreover, during clinical trials, researchers need to keep track of subjects’ progress by monitoring their participation and the quality of the data collected at specific phases of the trial. We have developed a visualization-based interface that assists the epidemiologists of a randomized clinical trial focused on the effects of lifestyle intervention in developing type 2 diabetes for patients with Gestational Diabetes Mellitus (GDM). Coaches are responsible for the intervention, and research assistants collect data from hundreds of questionnaires and clinical exams. We adopted user-centered design principles, which allowed continuous improvements to the visualizations and interactive features during a year-long development process. Besides typical selection and filtering features, the visualizations we have designed allow the research team to monitor each participant’s progress and perform analyses that facilitate findings in and between subjects’ histories. Two formal evaluations were also performed with experts and non-experts, where the visualization-based interface proved to be intuitive and useful for assisting coaching activities, monitoring the progress of data collection, and performing analyses.